Methods of applied fourier analysis - Ramanathan, Jayakumar (Springer New York, 1998)
This volume presents a development of the ideas of harmonic analysis with a special emphasis on application-oriented themes. In keeping with the interdisciplinary nature of the subject, theoretical aspects of the subject are complemented by in-depth explorations of related material of an applied nature. Thus, basic material on Fourier series, Hardy spaces and the Fourier transform are interwoven with chapters treating the discrete Fourier transform and fast algorithms, the spectral theory of stationary processes, H-infinity control theory, and wavelet theory.
Keywords: Fourier analysis